ANALISIS FAKTOR PENENTU RENDAHNYA MINAT BACA PELAJAR PADA PERPUSTAKAAN DAN ARSIP DAERAH DI KABUPATEN MIMIKA - Simon Seja; Ludia Panggalo (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study aims to determine the determinants of low reading interest of high school/vocational high school students in Mimika Regency. The method used in this study is a descriptive method. Data collection techniques in this study are observation techniques and distributing questionnaires to high school/vocational high school students in Mimika Regency. The analysis tool in this study uses factor analysis. Based on the results of the analysis, it shows that Technology factors, Environmental factors, and Facility factors are determinants of low reading interest of high school/vocational high school students in Mimika Regency.